Climatic and environmental changes during the middle to late Holocene in southern South America: A sclerochronological approach using the bivalve Retrotapes exalbidus (Dillwyn) from the Beagle Channel. (7th August 2015) - Gordillo, Sandra; Brey, Thomas; Beyer, Kerstin; Lomovasky, Betina J.
Abstract: Little is known about the effects of Holocene climate variability on marine environments and their biota in southern South America. Fossil shells of the aragonitic bivalve Retrotapes exalbidus (Dillwyn) offer the possibility of investigating climate variability and particularly the seasonal dynamics of sea-water temperature in the Beagle Channel during different parts of the middle to late-Holocene. We compared three specimens of different geological age (determined by 14 C), i.e. 5190 BP, 3839 BP, and 431 BP. These shells, respectively, refer to a cooling period at ca. 5000 BP, a climate optimum at ca. 4000 BP, and a further cooling at ca. 500 BP. All three shells showed clear annual growth bands, with a distinct intra-annual δ 18 O cycle. δ 18 O ranges clearly indicate higher summer temperatures in the 3839 BP shell (1.53‰–−1.16‰) compared with the 5190 BP shell (1.29‰–0.72‰) and the 431 BP shell (1.55‰–0.44‰), which correspond to maximum SSTs of 17.73 °C, 9.61 °C and 10.81 °C, respectively. Apparently, R. exalbidus shells are suitable bioarchives that allow comparing seasonal patterns through the Holocene, thus constituting another proxy for evaluating paleoclimatic and paleoenvironmental changes in this region.